Polyglycerolsulfate functionalized gold nanorods as optoacoustic signal nanoamplifiers for in vivo bioimaging of rheumatoid arthritis - Vonnemann, Jonathan; Beziere, Nicolas; Boettcher, Christoph; Riese, Sebastian B.; Kuehne, Christian; Dernedde, Jens; Licha, Kai; Von Schacky, Claudio; Kosanke, Yvonne; Kimm, Melanie; Meier, Reinhard; Ntziachristos, Vasilis; et al. (Theranostics, 2014)
We have synthesized a targeted imaging agent for rheumatoid arthritis based on polysulfated gold nanorods. The CTAB layer on gold nanorods was first replaced with PEG-thiol and then with dendritic polyglycerolsulfate at elevated temperature, which resulted in significantly reduced cytotoxicity compared to polyanionic gold nanorods functionalized by non-covalent approaches. In addition to classical characterization methods, we have established a facile UV-VIS based BaCl2 agglomeration assay to confirm a quantitative removal of unbound ligand. With the help of a competitive surface plasmon resonance-based L-selectin binding assay and a leukocyte adhesion- based flow cell assay, we have demonstrated the high inflammation targeting potential of the synthesized gold nanorods in vitro. In combination with the surface plasmon resonance band of AuNRs at 780 nm, these findings permitted the imaging of inflammation in an in vivo mouse model for rheumatoid arthritis with high contrast using multispectral optoacoustic tomography. The study offers a robust method for otherwise difficult to obtain covalently functionalized polyanionic gold nanorods, which are suitable for biological applications as well as a low-cost, actively targeted, and high contrast imaging agent for the diagnosis of rheumatoid arthritis. This paves the way for further research in other inflammation associated pathologies, in particular, when photothermal therapy can be applied. © Ivyspring International Publisher.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Dendritic polyglycerolsulfate; Gold nanorods; Inflammation; MSOT; Optoacoustic; Polyanion